The Influence of Online Promotion, Customer Trust, and Perceived Value on Repurchase Intention at Harper Premier Nagoya Batam - Oktavia Rahmadani; Azmen Kahar; Yonas Sara Lugistara (Pt. Threeple Herphi Educate, 2026)
This study aims to analyze the influence of online promotion, customer trust, and perceived value on guest repurchase intention at the Harper Premier Nagoya Hotel, Batam. The study employed a quantitative approach with a survey method. A sample of 150 respondents was selected using purposive sampling. The results show that consumer trust, perceived value, internet promotion, and repurchase intention are all generally in the good range. Perceived value has a significant negative impact on repurchase intention (β = −0.131; p = 0.039), but online promotion (β = 0.335; p < 0.001) and customer trust (β = 0.348; p < 0.001) have positive and significant effects. This negative correlation could mean that visitors' perceptions of the advantages have fallen short of their expectations in terms of cost, level of service, or overall experience. The measurement items, including any potential reverse-coded items, should be reexamined, and this result should be regarded cautiously. Online promotion, customer trust, and perceived value all had a substantial simultaneous impact on repurchase intention (F = 37.290; p < 0.001). The three factors account for 42.2% of the variance in repurchase intention, according to an Adjusted R² of 0.422. These results imply that improving customer trust and digital marketing tactics is crucial to boosting visitors' desire to return to the Harper Premier Nagoya Batam Hotel.